PENGARUH KOMBINASI PLASTICIZER TERHADAP KARAKTERISTIK EDIBLE FILM DARI KARAGENAN DAN LILIN LEBAH - (The Effect of Plasticizer Combination on Characteristics of Edible Film from Carrageenan and Beeswax) - Nok Afifah; Enny Sholichah; Novita Indrianti; Doddy A Darmajana (Balai Riset dan Standardisasi Industri Pontianak, 2018)
Edible film based on beeswax and carrageenan has been made using two types of plasticizers namely glycerol and sugar. Glycerol at a fixed concentration of 1% was combined with sugar (fructose, glucose and sucrose) each at three concentration levels of 0.5%, 1% and 1.5% w /vt. Edible film has water content, thickness, tensile strength, elongation and vapor transmission rate respectively 13.69-14.91%, 0.059-0.102 mm, 12.62-32.40 MPa, 13.34-43.57% and 17.65-25.38 g/m2/24 hours. The enhancement in plasticizer concentration resulted increasement of moisture content, thickness, elongation and water vapor transmission rate but decreased its tensile strength. All edible films showed lightness in range 84.45-85.61. Edible films with glycerol-sucrose plasticizer showed the lowest lightness. The scanning electron microscopy results indicated that edible films treated with plasticizer glycerol-fructose and glycerol-glucose have more homogeneous and smoother surface than edible control films and edible films with a glycerol-sucrose plasticizer.Keywords: edible film, fructose, glucose, plasticizer, sucrose ABSTRAKEdible film (lembaran tipis dapat dimakan) berbasis karagenan-lilin lebah telah dibuat dengan menggunakan dua jenis plasticizer (bahan pemlastis) yaitu gliserol dan gula. Gliserol pada konsentrasi tetap 1% dikombinasikan dengan gula (fruktosa, glukosa dan sukrosa) masing-masing pada tiga level konsentrasi yaitu 0,5%, 1% dan 1,5% b/vt. Edible film mempunyai kadar air, ketebalan, kuat tarik, elongasi dan kecepatan transmisi uap air masing-masing sebesar 13,69-14,91%, 0,059-0,102 mm, 12,62-32,40 MPa, 13,34-43,57% dan 17,65-25,38 g/m2/24 jam. Kenaikan konsentrasi plasticizer menghasilkan kenaikan kadar air, ketebalan, elongasi dan kecepatan transmisi uap air namun menurunkan kuat tariknya. Semua edible film menunjukkan sifat warna yang baik dengan lightness antara 84,45-85,61 sedangkan edible film dengan plasticizer gliserol-sukrosa memperlihatkan lightness paling rendah. Hasil scanning electron microscopy menunjukkan bahwa edible film yang diberi perlakuan Plasticizer gliserol-fruktosa dan gliserol-glukosa memiliki permukaan yang lebih homogen dan halus daripada edible film kontrol dan edible film dengan plasticizer gliserol-sukrosa. Kata kunci: edible film, fruktosa, glukosa, plasticizer, sukrosa